2009
DOI: 10.1093/cercor/bhp021
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Wrong Notes in Advance: Neuronal Correlates of Error Monitoring in Pianists

Abstract: Music performance is an extremely rapid process with low incidence of errors even at the fast rates of production required. This is possible only due to the fast functioning of the self-monitoring system. Surprisingly, no specific data about error monitoring have been published in the music domain. Consequently, the present study investigated the electrophysiological correlates of executive control mechanisms, in particular error detection, during piano performance. Our target was to extend the previous resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
137
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(153 citation statements)
references
References 108 publications
14
137
0
2
Order By: Relevance
“…Moreover, the use of mean amplitude measures for the pre-ERN, ERN, Pe and FRN is also compatible with previous ERP studies (e.g. Ridderinkhof et al, 2003;Ruiz et al, 2009;Yu and Zhou, 2009;Potts et al, 2010;San Martin et al, 2010;Dhar and Pourtois, 2011).…”
Section: Eeg Recording and Processingsupporting
confidence: 86%
See 4 more Smart Citations
“…Moreover, the use of mean amplitude measures for the pre-ERN, ERN, Pe and FRN is also compatible with previous ERP studies (e.g. Ridderinkhof et al, 2003;Ruiz et al, 2009;Yu and Zhou, 2009;Potts et al, 2010;San Martin et al, 2010;Dhar and Pourtois, 2011).…”
Section: Eeg Recording and Processingsupporting
confidence: 86%
“…This control analysis confirmed that the pre-ERN component was still visible (though slightly reduced) for commission errors in comparison to hits, when RTs were matched between conditions (hence when neutralizing potential stimulus-locked ERP effects), making it unlikely that the pre-ERN was mainly driven by a differential component overlap across conditions. Altogether, the results of these extensive control analyses suggest that this pre-response ERP component likely reflects error likelihood, being larger for risky (i.e., fast) decisions relative to safer (i.e., slower) perceptual decisions (see also Ruiz et al, 2009). …”
Section: Erpsmentioning
confidence: 80%
See 3 more Smart Citations